EFFECT OF ENTREPRENEURSHIP CHARACTERISTICS OF FISH FARMER ENTREPRENEURIAL INTENTIONS SEEDLING PEOPLE ON THE UNIT (UPR) SUMBERMINA SUSTAINABLE IN VILLAGE SUMBERSEKAR DISTRICT DAU MALANG - Haris Mahmudi; Agus Tjahjono; Zainal Abidin (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2017)
Development of entrepreneurship is seen as a strategic step in solving the nation's economic problems (Milla, 2013). According to Krueger, Reilly and Casrud (2000), stated that entrepreneurship is the kind of behavior that was planned very precisely when explained using the theory of intentions. The purpose of this study was to knowing the profile and business activities of fish farmers in the UPR Sumbermina Lestari, knowing the characteristics of entrepreneurship and entrepreneurial intentions of UPR Sumbermina Lestari, and analyze the influence of entrepreneurial characteristics with entrepreneurial intentions both partially and simultaneously. This research is descriptive. The data used is quantitative data and qualitative data. Source data used are primary data and secondary data. The object of research in the form of entrepreneurial characteristics consisting of innovation, need for achievement, internal locus of control, risks taking, tolerance for ambiguity, self confident, and future-oriented as a variable X with the intention of entrepreneurship as a variable Y. research instruments testing using three test was validity and reliability test, and test assumptions multikolinieritas. There are two methods of data analysis in this study, descriptive statistical analysis, and logistic regression analysis. Key words: Entrepreneurship, Characteristics of Entrepreneurship, Entrepreneurship Intention